The complete Apache Groovy developer course (Packt Publishing, 2019)
"Apache Groovy is a powerful, optionally typed and dynamic language, with static-typing and static compilation capabilities for the Java platform, aimed at improving developer productivity thanks to a concise, familiar and easy to learn syntax. It integrates smoothly with any Java program and immediately delivers to your application powerful features, including scripting capabilities, Domain-Specific Language authoring, runtime, and compile-time meta-programming and functional programming. This course is really designed for 2 different types of people and he thinks you will both benefit from it. If you're a beginner programmer with a some experience in another language like Python or Ruby, this course is for you. Dynamic languages are generally thought of as easier for total beginners to learn because they're flexible and fun. If you're an existing Java Developer (Beginner or Experienced), this course is also for you. You will learn Groovy compliments the Java language and makes some of the complex tasks from Java concise and easy."--Resource description page